Enrichment of Soymeal Medium to Increase the Rapamycin Production by Streptomyces hygroscopicus: Rapamycin Enhancement by Soymeal - Ali Hamdy, Abdel-Hamid; Ahmed, Essam Mohamed; Sallam, Lotfy Abd El-Raouf; Mohamed, Mohamed Abdelaziz (Biological Sciences - PJSIR, 2014)